Testing for Indeterminacy: An Application to U.S. Monetary Policy: Reply - Lubik, Thomas A; Schorfheide, Frank (American Economic Review, 2007)
Testing for Indeterminacy: An Application to U.S. Monetary Policy: Reply by Thomas A. Lubik and Frank Schorfheide. Published in volume 97, issue 1, pages 530-533 of American Economic Review, March 2007